NEW METHODOLOGY OF TARIFF CALCULATION FOR DOMESTIC CONSUMERS - PL.Somasundaram, M.Devanandhini , G.Elamathi , D.Sadhura (International Journal of Advanced Science and Technology, 2020)
This paper proposes the tariff calculation based on the reactive power consumption. Nowadays the electric appliances like lamp, motor and air conditioner plays the major role in our daily life. In such manner, most of the people does not know about their energy consumption and also unaware of their electricity bill calculation. In our project, we are going to calculate the tariff rate using the reactive power consumption. Here, the voltage and current sensor act as a input and we are going to interface the microcontroller and the LCD module. The purpose of microcontroller is to measure the power from the input and according to the power factor value we can calculate the reactive power consumption. The tariff rate is measured according to the reactive power consumption. The required tariff rate is displayed on the LCD module.